STRATEGI PENGUATAN PENDIDIKAN AGAMA PADA SEKOLAH ISLAM TERPADU - Jihan - (Paedagogia: Jurnal Pendidikan, 2019)
This study discusses the strategy of strengthening religious education in Qurrota A'yun Islamic Elementary School (SDIT) in Marawola Subdistrict, Sigi Regency, with the problem is how the model of religious education learning in Qurrota A'yun Islamic Elementary School (SDIT) in Marawola Subdistrict, Sigi Regency. What is the strategy of strengthening religious education in the Integrated Islamic Elementary School (SDIT) Qurrota A’yun Marawola District Sigi Regency ?. This study used qualitative research methods. The research results are a model of religious education learning in SDIT Qurrota A’yun is to implement an integrated curriculum, namely between religious and general subjects, where the curriculum is designed by integrating Islamic values ​​in learning activities. While the strategy of strengthening religious education at SDIT Qurrota A’yun was carried out in two activities namely learning and habituation. Learning activities are carried out through curricular learning and extracurricular learning.